Analisis Kepuasan Pasien di RSU Baros terhadap Aplikasi Mobile JKN - Wantias, Isni; Yuliaty, Farida (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
This research examines the factors that influence patient satisfaction with the Mobile JKN application at RSU Baros and its impact on perceptions of overall health service quality. Through comprehensive literature analysis, five main factors influencing patient satisfaction were identified: ease of use, security and privacy, quality of information, responsiveness and technical support, and integration with physical health services. The results of the study show that satisfaction with the Mobile JKN application is positively correlated with patient perceptions of the quality of health services at RSU Baros. Key challenges include the digital divide, data security, and systems integration, while opportunities include personalization of services, telemedicine integration, and increased health literacy. This research highlights the importance of a holistic approach in digital health application development, considering not only technical aspects but also user needs and preferences. The implications of this research include recommendations for continuous improvement of the Mobile JKN application, strategies for overcoming implementation challenges, and utilizing technological opportunities to improve the quality of health services in the digital era.